Corruption in Chilean prisons and its predictors from the perspective of incarcerated people - Sanhueza, Guillermo E. (2024)
Although corruption within prisons is not necessarily a new phenomenon, this article offers, through quantitative data from a survey (MQPL questionnaire adapted to Chile) applied in 2022 in 20 Chilean prisons (n = 1,159), an empirical view of it from the perspective of incarcerated individuals and offers an exploration of its predictive factors. The perception of corruption was operationalized through the dependent variable “in this prison things move with money”, which was modeled through multiple linear regression, where various predictors were incorporated into the model, which was able to explain 32.5% of the variation in the perception of corruption. The independent variables negatively associated with corruption were the perception of good functioning of the prison, the existence of clear rules within the prison, the perception of receiving fair treatment and respect for rights and living in a concessioned prison (privately operated facility). On the other hand, the predictors directly associated with a perception of greater corruption were the perception of a tense atmosphere in prison, abuse towards weaker inmates, and the perception of fear for one's own physical integrity. Implications of the findings are discussed to improve prisons.